AB0954 Safety of Joint Puncture in Patients Anticoagulated with Acenocumarol. (10th June 2014) - Guillen Astete, C.A.; Bouroncle Alaluna, C.; Boteanu, A.; Blazquez Cañamero, M.; Zea Mendoza, A.
Abstract : Background: The diagnostic and therapeutic management of patients with joint pathology in the emergency department often includes the need for joint punctures. On the other hand, anticoagulant therapy often generates resistance to perform these procedures because of the risk of bleeding. This resistance is a major obstacle when assessing or treating joint complains considering that it is estimated that about 12 per 1000 people in Spain are receiving oral anticoagulants. This resistance, however, does not seem to be supported by the few studies conducted with warfarin, however it conditions a delayed diagnosis with a potential risk of irreparable joint damage or serious complications. No studies have been conducted to measure this risk in patients using acenocoumarol. Objectives: The purpose of this study is to determine the rate of bleeding complications in patients anticoagulated with acenocoumarol according to the international normalized ratio (INR) index of coagulation. Methods: A retrospective study was performed with 901 records of patients who underwent a puncture joint from 2009 to 2013. Records were grouped on the basis of having INR index higher or lower than 2.0 (268 and 633 records, respectively). The rate of bleeding complications was performed using chi-square test. Results: A 0.37% rate of early bleeding complications (<24 hours) in the group of patients with INR <2 and a rate of 0.99% in the group of patients with INR > or =2 was observed (p=0.47). Only one case of tardive bleeding complication was detected (between 24 hours and 30 days) in the group of patients with INR > or =2. A need for medical reassessment due to pain was observed in 5.22% of patients with INR <2 and 3.44% of patients with INR > or =2 (p>0.05). Conclusions: This is, to our knowledge, the first study aimed at determining the presence of complications related to joint puncture in anticoagulated patients with acenocoumarol according to the INR index. Based on our results we consider that the use of acenocoumarol at therapeutic doses not mean an increased risk of bleeding when performing arthrocentesis or joint infiltration and therefore delay these procedures until reversion of the INR is an unnecessary behavior. The few available studies, conducted with warfarin agree that there are no statistically significant differences in the rate of bleeding complications according to the INR at the time of the procedure. The results of our study are consistent with those obtained by Ahmed et al. (Am J Med 2012; 125[3]:265-9) in terms of early and late bleeding complications in warfarin users, however, in our study consultation motivated by pain was much higher in both groups. This increase could be explained by the fact that a significant proportion of patients whose records were included came from an area where access to emergency reassessments are relatively easy. Thumboo et al. (Arthritis Rheum 1998; 41[4]:736-9) and Salvati et al. (Reumatismo. 2003; 55[3]:159-63) published similar prospectives studies with smaller sample sizes, however both authors demonstrated a low rate of bleeding complications in warfarin users and confirm the safety of these procedures practice without reverse anticoagulation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5859